Numerical simulation of deformation and fracture of metals under plane shock wave loading - Saveleva, Nataliya Vladimirovna; Bayandin, Yurii Vitalievich; Naimark, Oleg Borisovich (Computational Continuum Mechanics, 2012)
The mathematical model capable of describing the behavior of materials subjected to shock loading has been developed earlier in the framework of the statistical theory of medium with defects. In the present work, this model is modified and a criterion for determining the conditions of spall fracture is proposed. The base theory treats deformation and fracture as the evolution of defect structures, which allows us to choose the necessary criterion. Numerical algorithms yield free surface velocity profiles. The analysis of these algorithms shows the effect of loading parameters on the strength characteristics of the material.
Keywords: shock wave; defect; free surface velocity